Model Pendidikan Agama Kristen dalam Mengembangkan Masyarakat Majemuk di Indonesia - Manalu, Immanuel Lando; Iswahyudi, Iswahyudi; Valentina, Lista; Bintoro, Wahyu; Pasaribu, Damaria (Indonesian Journal of Religious, 2023)
A Christian education model that aims to develop a pluralistic society in Indonesia characterized by inclusivity, interfaith dialogue, and ethical values. In the context of a plural and pluralistic Indonesia, this model emphasizes interfaith dialogue and understanding, fosters respect for religious and cultural diversity, promotes ethical values and social justice, and encourages active involvement in community service. By applying this model, Christian religious education can play an important role in fostering a society where individuals from different backgrounds can coexist harmoniously, value diversity, and contribute to the common good. The proposed model offers a framework for educators, policymakers, and religious leaders to develop effective strategies and initiatives that promote understanding, respect, and cooperation among different religious and cultural communities in Indonesia. Therefore, the development of an inclusive and multicultural PAK model is the right approach in fostering mutual acceptance of each other in the context of a pluralistic society. This research uses a literature review method that refers to a theory in literature sourced from articles, books, and other scientific works.   Model Pendidikan Agama Kristen yang bertujuan untuk mengembangkan masyarakat majemuk di Indonesia yang bercirikan inklusivitas, dialog antar agama, dan nilai-nilai etis. Dalam konteks Indonesia yang majemuk dan majemuk, model ini menekankan dialog dan pemahaman antar agama, menumbuhkan rasa hormat terhadap keragaman agama dan budaya, mengedepankan nilai-nilai etika dan keadilan sosial, serta mendorong keterlibatan aktif dalam pelayanan masyarakat. Dengan menerapkan model ini, Pendidikan Agama Kristen dapat memainkan peran penting dalam membina masyarakat di mana individu dari berbagai latar belakang dapat hidup berdampingan secara harmonis, menghargai keragaman, dan berkontribusi pada kebaikan bersama. Model yang diusulkan menawarkan kerangka kerja bagi para pendidik, pembuat kebijakan, dan pemimpin agama untuk mengembangkan strategi dan inisiatif yang efektif yang mempromosikan pemahaman, rasa hormat, dan kerja sama di antara komunitas agama dan budaya yang berbeda di Indonesia. Maka dari itu, pengembangan model PAK yang inklusif dan multikultural menjadi pendekatan yang tepat dalam membina sikap saling menerima satu sama lain dalam konteks masyarakat majemuk. Penelitian ini menggunakan metode kajian pustaka yang merujuk kepada sebuah teori secara literatur yang bersumber dari artikel-artikel, buku-buku, dan karya ilmiah lainnya.